A Versatile Self‐Organization Printing Method for Simplified Tandem Organic Photovoltaics. (30th April 2016) - Kim, Seok; Kang, Hongkyu; Hong, Soonil; Lee, Jinho; Lee, Seongyu; Park, Byoungwook; Kim, Junghwan; Lee, Kwanghee
Abstract : Despite recent dramatic enhancements in power conversion efficiencies (PCEs) resulting in values over 10%, the manufacturing of tandem organic solar cells (OSCs) via current printing technologies is subject to tremendous challenges. Existing complicated tandem structures consisting of six or more component layers have been a major obstacle that significantly increases the complexity of printing processes and substantially sacrifices the PCE for printed devices. Here, an innovative printing method is reported that simplifies the fabrication process of the tandem OSCs. By developing a new printing technique using a nanocomposites containing interfacial and photoactive materials, a simultaneously printed bilayer of consisting of interfacial and photoactive layers, achieved through vertical self‐organization, is successfully demonstrated, resulting in tandem OSCs with only four printed layers. Moreover, by rigorously controlling the molecular weight of the interfacial materials, the self‐assembly characteristics are improved and an efficient tandem OSC is yielded with a PCE of 9.1% achieved in printed layers. Abstract : Efficient and simplified tandem organic solar cells are demonstrated through a new self‐assembly printing technique using a spontaneous vertical phase separation. A bilayer of interfacial and photoactive layers is simultaneously printed by improving vertical self‐organization characteristics. A high tandem efficiency of 9.1% is obtained with a four‐layer tandem structure.